2016
DOI: 10.1177/2167696816641542
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Bias in Research on Friendship Among Emerging Adults

Abstract: Five studies (N ¼ 5,150) relying on an exhaustive procedure addressed whether volunteer bias (VB) exists in friendship research among emerging adults (EAs). Consistently, the studies showed that women are more willing than men to participate in research on same-sex best friendship (SSBF). Studies 2 through 5 showed that friendship duration is not related to volunteering. Studies 3 and 4 showed that the friendships of volunteers were higher in positive friendship experiences compared to nonvolunteers. Finally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 81 publications
2
12
0
Order By: Relevance
“…Our observation that women tended to volunteer at a higher rate than men is consistent with other studies [84,85,86,87,88,89]. We found that increasing compensation to an amount similar to the local minimum wage ($U.S.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation that women tended to volunteer at a higher rate than men is consistent with other studies [84,85,86,87,88,89]. We found that increasing compensation to an amount similar to the local minimum wage ($U.S.…”
Section: Discussionsupporting
confidence: 92%
“…Another limitation is risk of potential volunteer bias. A study on close relationships may attract more females than males or may attract participants who have fairly positive relationships overall (Demir, Haynes, Orthel-Clark, & Ozen, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Our sample was also largely racially White and female, which precluded the analysis of race- and gender-related effects in our statistical models. Future researchers should consider how to recruit more racially and ethnically diverse samples and males (especially given robust evidence of gender-related volunteer bias in studies examining emerging adults’ social relationships; see Demir, Haynes, Orthel-Clark, & Özen, 2017). However, despite a lack of males in the present study, we note the overwhelming paucity of gender- specific hypotheses and findings in recent studies on attachment dynamics in emerging adulthood, suggesting that gender may not be a major moderator (e.g., see Bernier et al, 2005; Larose, Bernier, & Tarabulsy, 2005; Scharfe & Cole, 2006).…”
Section: Discussionmentioning
confidence: 99%